Stuck at zero: Price rigidity in a runaway inflation - Avichai Snir; Haipeng Chen; Daniel C. Levy (Bar-Ilan University, Department of Economics, 2021)
We use micro level retail price data from convenience stores to study the link between 0-ending price points and price rigidity during a period of a runaway inflation, when the annual inflation rate was in the range of 60%-430%. Surprisingly, we find that 0-ending prices are less likely to adjust, and when they do adjust, the average adjustments are larger. These findings suggest that price adjustment barriers associated with round prices are strong enough to cause a systematic delay in price adjustments even in a period of a runaway inflation, when 85 percent of the prices change every month.
Keywords: E31; L16; 330; Sticky Prices; Rigid Prices; 0-Ending Price Points; 9-Ending Price points; Runaway Inflation; Cost of Price Adjustment; Menu Cost